Water pollution - Gay, Kathlyn (New York : F. Watts, 1990)
Discuss the problem of our contaminated rivers, lakes, and oceans and proposes ways to purify them.
Keywords: Water -- Pollution -- Juvenile literature; Water quality management -- Juvenile literature; Water pollution; Water quality management